2011
DOI: 10.1136/adc.2011.212563.203
|View full text |Cite
|
Sign up to set email alerts
|

Playing with fire: missed opportunities in the referral and follow-up to pre-school burns

Abstract: Aims Every year in the UK, 50 000 children <5 years sustain burns. Health visitor (HV) follow-up after injury attendances to emergency departments (ED) signifi cantly reduces further injury, improves home safety practices and reduces hazards, and may identify potential safeguarding concerns. We evaluated ED burns referrals to HV, to identify what follow-up occurs and the factors infl uencing this decision. Methods All pre-school burn attendances to ) were identifi ed. A postal questionnaire was sent to HVs, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research has shown that over half of notifications to HVs about ED attendances for child injury did not result in any action (Kendrick et al, 2001). A survey of 82 HVs of children who attended an ED with a burn found that information contained in notifications was variable and lacking in detail, and HVs had to use their own knowledge of the family to inform decisions regarding further action (Saunders et al, 2011). A recent study demonstrated that, for children attending ED settings with a burn, key risk factors for child maltreatment included on a standardised, evidence‐based burns proforma were often not identified or recorded by ED clinicians (Nuttall et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that over half of notifications to HVs about ED attendances for child injury did not result in any action (Kendrick et al, 2001). A survey of 82 HVs of children who attended an ED with a burn found that information contained in notifications was variable and lacking in detail, and HVs had to use their own knowledge of the family to inform decisions regarding further action (Saunders et al, 2011). A recent study demonstrated that, for children attending ED settings with a burn, key risk factors for child maltreatment included on a standardised, evidence‐based burns proforma were often not identified or recorded by ED clinicians (Nuttall et al, 2020).…”
Section: Discussionmentioning
confidence: 99%